Enhancement of ADC accuracy with redistribution of the charge at the expense of weight redundancy usage - Zakharchenko, S. M. (Visnyk of Vinnytsia Politechnical Institute, 2010)
New digital method of ADC self-calibration with charge redistribution is described. The method is based on the usage of weight redundancy and is characterized by considerable reduction of methodical error. Analytical relations for computation of corrections are obtained.